The Role of Èngghi-Bhunten Madurese Language Communication in Shaping Children's Morals Parental Preferences in Rural Communities - Mohamad Sudi,; Zaedun Naim,; Ahmad Iwan Zunaih,; Fahmi Reza Alfani,; Mutaallim, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Èngghi-bhunten (E-B) is the most refined form of the Madurese language (ML), used when speaking to respected individuals or those considered noble, such as Kyai or members of a pesantren family. The use of E-B aims to express respect and appreciation in communication. This study examines the role of E-B language in shaping children's morality, particularly in relation to preferences within rural communities. E-B not only serves as a means of communication but also as an important cultural tool in the process of socialization. In rural Madurese communities, parents tend to prioritize the use of this language to instill values and moral principles in their children. This research aims to understand how language, particularly E-B, reflects and reinforces social norms, ethical behavior, and traditional values within society. By analyzing interactions between parents and children, this study reveals the close relationship between language choice and moral teaching as well as parental guidance. This research employs a qualitative approach, with data consisting of words, phrases, and sentences obtained from the rural community. Data collection techniques include simak libat cakap method. It involves listening to and recording interactions in the community and conducting interviews with key figures. The findings show that the use of E-B significantly contributes to the formation of morality in the community, especially for children in rural areas. The use of E-B also plays a crucial role in shaping children's behavior, particularly in fostering respect, responsibility, and social harmony. This research provides in-depth insights into the role of language in children's moral development, particularly within the context of specific cultures. The study reveals how parents use language to transmit moral values and how language preferences are influenced by existing cultures. Additionally, this research enriches the study of language and socialization by showing that language functions not only as a communication tool but also as a means to shape children's attitudes and moral behavior